Analisis Efektivitas Kebijakan Pemungutan Pajak Reklame Dalam Rangka Meningkatkan Kepatuhan Wajib Pajak Dan Penerimaan Negara Pada Badan Pendapatan Daerah Jakarta Pusat - Feninda Amalia Putri; Alief Ramdhan (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
This research aims to analyze the effectiveness of the advertising tax policy in enhancing taxpayer compliance and government revenue at the Central Jakarta Regional Revenue Agency, as well as to identify the hindering and driving factors affecting the effectiveness of the advertising tax. The research adopts a qualitative methodology, utilizing both primary and secondary data. Data collection techniques include interviews, observations, and document analysis. The findings reveal that the implementation of the Advertising Tax Collection Policy in enhancing compliance and government revenue at the Central Jakarta Regional Revenue Agency fluctuates due to economic factors and a lack of understanding regarding the advertising tax categories. Moreover, there is a notable lack of taxpayer curiosity towards advertising tax collection. Efforts should be made to improve information dissemination and education by providing engaging and clear explanations of the advertising tax.